Understanding child maltreatment an ecological and developmental perspective - Scannapieco, Maria; Connell-Carrick, Kelli (Oxford : Oxford University Press, 2005)
This volume examines the impact of child maltreatment at each stage of a child's development, including infancy, early childhood, middle childhood, and adolescence. This book proposes assessment and intervention strategies based on a deep understanding of each stage of a child's development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child abuse; Child development; Family assessment; Risk assessment; Family social work